The Family in Early Modern England - Berry, Helen (Cambridge University Press, 2013)
The selection of a theme for a volume of essays dedicated to our teacher, mentor and friend Anthony Fletcher was a peculiarly difficult task. His contribution to the field of early modern history has, in the course of a lifetime’s career, encompassed a wide range of research interests. From his early studies on county history, notably of Sussex, to his powerful and meticulous account of the outbreak of the English Civil War, from his analyses of the dynamics of office-holding among local magistrates and county gentry, to the influence of the Protestant religion upon household and government in the early Stuart period, it is extremely difficult to categorise him as a particular type of historian. His name is familiar to most former ‘A’ level history students as the author of Tudor Rebellions (now in its fifth edition), a book which first inspired many young people to study early modern history through its engagement with archival material and clear communication of the excitement of interpreting primary historical documents. The impact of this book nationally was brought home at one of the present author’s weddings, where a guest (a former ‘A’ level history student, now turned city lawyer and not usually given to over-excitement) glanced at the seating plan and exclaimed ‘That’s not the Anthony Fletcher is it?’